1995
DOI: 10.1074/jbc.270.51.30479
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Autolytic Cleavage Can Contribute to the Activation of Progelatinase A by Cell Membranes

Abstract: Membrane-type matrix metalloproteinase (MT-MMP) messenger RNA and protein expression were shown to be elevated in human fibroblasts following treatment with concanavalin A, coincident with the induction of the ability to process progelatinase A.CHO cells transfected with the cDNA for MT-MMP were able to process both wild type progelatinase A and a catalytically inactive mutant, E375A progelatinase A. Both proenzymes were converted to a 68-kDa intermediate (reducing gels) form, but only the wild type enzyme was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
188
1
9

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(207 citation statements)
references
References 25 publications
9
188
1
9
Order By: Relevance
“…4, lanes denoted 'E/A' and 'E/A+MT', respectively). This is consistent with the previous observation that a catalytically inactive mutant progelatinase A was converted to an intermediate form by incubation with CHO cells expressing MT1-MMP [25].…”
Section: Resultssupporting
confidence: 93%
“…4, lanes denoted 'E/A' and 'E/A+MT', respectively). This is consistent with the previous observation that a catalytically inactive mutant progelatinase A was converted to an intermediate form by incubation with CHO cells expressing MT1-MMP [25].…”
Section: Resultssupporting
confidence: 93%
“…IB, lane 1). This latter band represents an intermediate activated form of MMP-2 which has been previously shown to result from a MT1-MMP-depen-dent proteolytic processing of pro-MMP-2 [20,31,32]. After 48 h, the amount of 62-kDa MMP-2 increased in both conditioned medium and cell extract [accounting for 10 and 35% of total MMP-2 activity, respectively (Figs.…”
Section: Ecm Components Modulate Pro-mmp-2 Activationmentioning
confidence: 79%
“…It can be hypothesized that type IV collagen mediates its effect by bringing closer cell membrane-associated MT1-MMP/TIMP-2/MMP-2 complexes, therefore promoting the intermolecular autolytic cleavage of intermediate MMP-2 and thus leading to the generation of the fully mature species. Additionally, type IV collagen decreases the level of secreted TIMP-2, thus potentially furthering the processing of pro-MMP-2 which is known to be inhibited by high TIMP-2 concentrations [20,31,53]. It is worth noting that the TIMP-2 degradation process illustrated here potentially represents an additional regulatory mechanism of the proteolytic activity of the cells.…”
Section: Type IV Collagen-mediated Mmp-2 Activation Is Associated Witmentioning
confidence: 82%
See 1 more Smart Citation
“…This finding is interesting, because it has been suggested that, after the MT1-MMP-mediated conversion of the 72-kD form of MMP-2 into the 68-kD intermediate form, an autoproteolytic activation step is required for the final activation of MMP-2, resulting in the 66-kD form. [25][26][27] Our data indicate that a considerable fraction still is activated, despite the absence of active MMP-2. The higher level of the intermediate form of MMP-2 (68 kD) under these conditions suggests that this repre- sents the fraction activated by MMP-2 itself, indicating that, in addition to an autoproteolytic activation step, compensatory mechanisms may exist by which the intermediate form of MMP-2 may be converted into its fully activated, 66-kD form.…”
Section: Discussionmentioning
confidence: 58%